PENGEMBANGAN MEDIA GAME EDUKASI JELAJAH DISTRIK (JETRIS) BERBASIS GAME-BASED LEARNING TERHADAP KEMAMPUAN SPASIAL SISWA KELAS IV SEKOLAH DASAR PADA PEMBELAJARAN IPS MATERI PETA - Muhammad Alif Nur Shafwan Laksono; Putri Rachmadyanti (STKIP Subang, 2026)
The dominance of passive learning methods has resulted in the low spatial abilities of fourth-grade elementary school students, particularly in interpreting directions, relative positions, and navigation routes in map materials. Responding to this issue, the focus of this research is to produce the Jelajah Distrik (JETRIS) educational game media based on Game-Based Learning, and to evaluate its validity, effectiveness, and practicality upon use. This research applies a Research and Development (R&D) approach using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Data collection involved 22 fourthgrade students at SDN Kramatjegu 1 as subjects for a limited trial. The feasibility analysis indicates that this media is highly valid, achieving a percentage of 82.14% from material experts and 91.67% from media experts. In terms of practicality, JETRIS achieved a score of 89.61%, categorized as highly practical based on the accumulation of educator and student response questionnaires. Furthermore, the media successfully provided a tangible improvement in spatial ability scores, marked by a surge in the average pre-test score from 59.32 to a post-test average of 80.91, alongside a class N-Gain test score of 0.53 in the medium (quite effective) category. In conclusion, the developed JETRIS media has proven its validity, effectiveness, and practicality as an interactive learning tool innovation to train students' spatial abilities contextually